The concept of metropolitan border regions: Development, strategies and new directions - Andrea Hartz (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
In recent decades the challenges of globalisation, European integration and strengthened regionalisation have led to a reassessment of metropolitan regions. In Germany, the guiding principles issued by the Conference of Ministers for Spatial Planning in 2006 provided an occasion on which to rethink the role of border regions in the context of the discourse on metropolises. The metropolitan potential of border regions is far from fully exploited. This is particularly true in relation to cross-border spatial development. The concept of metropolitan border regions could be a promising way of intensifying cross-border cooperation and territorial integration. A precondition for this is that metropolisation strategies are proactively pursued using key measures and that existing structures of cooperation are further developed towards 'metropolitan' governance.
urn:nbn:de:0156-40970753; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Metropolitan border regions; border regions; metropolitan regions; metropolitan governance; metropolisation strategies; metropolitan areas; (cross-border) regional development